(untitled) (Ustozlar uchun, 2026)
The presence of teeth, whether complete or partial, is a major etiological factor influencing the oral ecology [1]. Specific habitats for microbial growth and activity are found in dental fissures, carious cavities, root canals, gingival sulci, and dental plaque. The environmental conditions for the oral microbiota undergo significant alterations following partial or total tooth loss and the subsequent introduction of dental prostheses [2].